The effect of changing one’s country of residence on the decision to become an organ donor: the experience of religious immigrant women living in Sweden - Ferid Krupić; Sahmir Šadić; Svemir Čustović; Mahir Jašarević; Mirsad Fazlić; Kristian Samuelsson (Medicinski glasnik, 2018)
Aim: To explore and elucidate women's knowledge of and willingness to take part in organ donation, and to explore if their opinions were changed by coming to Sweden. Methods: The study was designed as a qualitative study using data from interviews with women from Bosnia and Herzegovina, Macedonia, Croatia and Kosovo. The inclusion criteria were women who were immigrants in Sweden and have lived in Sweden for more than 10 years. Five groups including forty-five women were invited to participate in the study and 39 agreed. The women were aged 29 to 73 years (mean 52.5 years). Results: Regarding knowledge and information about organ donation, most women found it very important to be able to talk about such things. However, the knowledge and information about organ donation of almost all the women was at a very low level. None of the women changed their opinion on the organ donation and attitudes from their countries of origin. All women firmly emphasized and explained that by coming to another state they do not become a different person and retain all values they had and with which were born in home country. Conclusion: It is important to study how to find new ways to communicate and work with minorities and vulnerable groups in order to discuss organ donation with all those who could be potential donors in the Swedish health care system.
Keywords: organ donation; anthropological aspects; knowledge; gender; immigrants; qualitative research